2010
DOI: 10.1002/ajp.20910
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mineral lick visitation by spider monkeys and howler monkeys in Amazonia: are licks perceived as risky areas?

Abstract: Mineral licks--also known as "salados," "saladeros," or "collpas"--are specific sites in tropical and temperate ecosystems where a large diversity of mammals and birds come regularly to feed on soil. Although the reasons for vertebrate geophagy are not completely understood, animals are argued to obtain a variety of nutritional and health benefits from the ingestion of soil at mineral licks. We studied the temporal patterns of mineral lick use by white-bellied spider monkey (Ateles belzebuth) and red howler mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 45 publications
(67 reference statements)
3
50
0
2
Order By: Relevance
“…For spider monkeys, a folivorous diet might increase the amount and diversity of toxins and secondary metabolites consumed, which could have both direct and indirect influences on their nutrition and health. It may be significant, then, that in most long-term studies spider monkeys are reported to feed on clay from mineral licks (Izawa 1993, Link et al 2011a, which is suggested to be one means by which they cope with the effects of secondary metabolites. Spider monkeys at San Juan and elsewhere are also reported to feed on decayed wood from dead standing trees (Suarez 2006, Di Fiore et al 2008, Chaves et al 2012, which may allow them ac cess to additional minerals not otherwise available in their diet (Krishnamani & Ma haney 2000, Ferrari et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For spider monkeys, a folivorous diet might increase the amount and diversity of toxins and secondary metabolites consumed, which could have both direct and indirect influences on their nutrition and health. It may be significant, then, that in most long-term studies spider monkeys are reported to feed on clay from mineral licks (Izawa 1993, Link et al 2011a, which is suggested to be one means by which they cope with the effects of secondary metabolites. Spider monkeys at San Juan and elsewhere are also reported to feed on decayed wood from dead standing trees (Suarez 2006, Di Fiore et al 2008, Chaves et al 2012, which may allow them ac cess to additional minerals not otherwise available in their diet (Krishnamani & Ma haney 2000, Ferrari et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…At Serranía de Las Quinchas, an inter-Andean forest site in northern Colombia, brown spider monkeys fed almost exclusively on ripe, fleshy fruits all year (Link et al 2012) and only complemented their diet with leaves and other items for approximately 6% of the time they spent feeding. Spider monkeys at Las Quinchas frequently visit mineral licks, in a similar pattern to the behavior of spider monkeys in western Amazonia (Izawa 1993, Link et al 2011a, to obtain complementary nutrients or minerals not readily available in their diets or to mitigate the effects of secondary metabolites contained in leaves and other vegetative parts of plants (Krishnamani & Mahaney 2000).…”
Section: Introductionmentioning
confidence: 88%
“…One of the challenges facing many smallholder livestock producers is inability to satisfy mineral requirement of their animals leading to reduced productivity [8] More than 50 species of animals in the world have been reported to ingest various types of earth materials in the natural licks [9]. The reasons for consuming the licks are not clearly understood, but animals are argued to obtain both nutritional and health benefits [10]. Some perceived benefits from natural licks to the animals are; sources of minerals and to alleviate the effects of digestive disorders and toxic plant secondary metabolites [11].…”
Section: Introductionmentioning
confidence: 99%
“…Os primatas neotropicais são mamíferos arborícolas (Heymann, 1998), cujos eventos de uso do chão têm sido relacionados, principalmente, a contextos de fragmentação do habitat e exploração de recursos específicos (Schön-Ybarra, 1984;Fragaszy, 1986;Mendes, 1989;BiccaMarques e Calegaro-Marques, 1995;Almeida-Silva et al, 2005;Defler, 2009;Haugaasen e Peres, 2009;Spagnoletti et al, 2011;Link et al, 2011;Barnett et al, 2012). Mourthé et al (2007) propõem que a perturbação do habitat e a presença de pesquisadores parecem facilitar o uso do chão por muriquis-do-norte habituados na Reserva Particular do Patrimônio Natural Feliciano Miguel Abdala em Caratinga (MG), enquanto Tabacow et al (2009) sugerem que o comportamento desta população representa uma expansão de nicho em um habitat fragmentado, onde as oportunidades de dispersão são limitadas, facilitada por uma difusão da tradição entre os indivíduos.…”
Section: Paula Breves Austem Stravs Andrade Dias Alcides Pissinatti Junclassified